PHYSICAL CHARACTERISTICS AND SENSORY EVALUATION OF ROSELLE (HIBISCUS SABDARIFFA L.) BUTTERFLY PEA (CLITORIA TERNATEA L.) CORDIAL - Yoarisandi, Mico; Fuadi, Misril; Bin Saari, Saiful Bahri (Institute of Computer Science (IOCS), 2023)
The purpose of this research is to explore the application of rosella extract and butterfly pea as the main ingredient in cordial. This research focuses on physical characteristics and sensory evaluation. This study used a completely randomized design method with two extraction treatments and 10 replications. The results of this study indicate that cordial roseela telang flowers in color measurement using a refractometer have results in which treat A has the most superior color L (21.04), a* (14.10), and b* (6.10), and viscosity measurement using a viscometer tool gets the most superior results (41.74), pH measurement gets the most superior results (2.66), and TSS Brix measurement (56.24%). Taste test results and overall acceptance show that cordial with formulations A and B have the best physical properties